Relationship Between Education, Knowledge And Maternal Parity To Completeness Basic Immunization In Children At The Kalidoni Health Center Palembang - Rehana Rehana; Nurul Komariah; Rafika Efriza fatriance (CV. AFDIFAL MAJU BERKAH, 2026)
Immunization is an effort to provide immunity to babies and children by injecting vaccines into the body in order to make antibodies to prevent certain diseases. Then, a vaccine is a material used to stimulate the formation of anti-substances that are entered into the body through injections (for example the vaccines of Bacillus Calmette Guerin (BCG), Diphtheria, Pertussis and Tetanus (DPT) and Measles and through the mouth (for example the polio vaccine). To determine the relationship among education, knowledge and maternal parity with the completeness of children basic immunization at the Kalidoni Palembang Health Center in 2023.This research is an analytic survey research with a cross sectional approach. The study population was children aged ≥9-24 months who visited the immunization polyclinic at the Kalidoni Health Center in Palembang with a sample of 56 respondents who were taken using a purposive sampling technique. The research variables included the independent variables which are education, knowledge and maternal parity and the dependent variable, namely the completeness of basic immunization for babies. Univariate and Bivariate data analysis. Based on the results of bivariate analysis using the Chi Square statistical test, it was found that on the mother's education variable ρ value = 0.001 (ρ ≤ 0.05), on the mother's knowledge variable ρ value = 0.001 (ρ ≤ 0.05) and on the maternal parity variable ρ value = 0.001 (ρ ≤ 0.05). From the results of the study there are three variables which are education, knowledge and maternal parity having a significant relationship with the completeness of children basic immunization. There are three variables which are education, knowledge and maternal parity having a significant relationship with the completeness of children basic immunization.